Adiwiyata Program Reduced Activities in Training Mi Khadijah Students' Responsibility Skills in Malang City - Isnaini, Putri Karlia; Aziza, Imro'atul; Firdausyah, Siti Roudhotul; Ertanti, Devi Wahyu (Jurnal Ilmiah Mandala Education (JIME), 2025)
This research focuses on analyzing the implementation of the Adiwiyata program, specifically the "reduce" activities, in training students' responsibility skills at MI Khadijah Kota Malang. This research uses a quantitative approach with a case study method, collecting data through observation, interviews, and documentation. The research results show that the 'reduce' program successfully increased students' awareness of the importance of reducing plastic waste and single-use items. Students were involved in various activities such as bringing Tumblrs, sorting waste, and utilizing waste banks. This not only fosters an attitude of environmental care but also trains students' responsibility towards the environment. However, some students still lack awareness of the environment by using single-use bottles. This program provides significant benefits in creating a cleaner, healthier school environment and in building responsible character among students.